2018
DOI: 10.1016/j.esxm.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sexual Function and Positions in Women with Severe Obesity After Bariatric Surgery

Abstract: Introduction Severe obesity is most effectively treated with bariatric surgery. The resulting weight loss is expected to improve a variety of obesity-related conditions, including sexual dysfunction. Aim To analyze changes in the sexual function of women with obesity following bariatric surgery. Methods A prospective study was conducted between April 2015 and April 2016 involving 62 women with obesity who underwent Roux-en-Y gastric bypass. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 30 publications
3
19
1
3
Order By: Relevance
“…Recently, Olivera et al compared sex positions after bariatric surgery and found that the number of sex positions that the couples engaged in increased after the operation. FSFI and all subgroups showed significant improvement 27 . In our study, we found a significant improvement in FSFI and in all subdomains after surgery.…”
Section: Discussionsupporting
confidence: 69%
“…Recently, Olivera et al compared sex positions after bariatric surgery and found that the number of sex positions that the couples engaged in increased after the operation. FSFI and all subgroups showed significant improvement 27 . In our study, we found a significant improvement in FSFI and in all subdomains after surgery.…”
Section: Discussionsupporting
confidence: 69%
“…The women in this study had a higher level of education than in the studies of Oliveira et al 15 and Sarwer et al 16 , in which, respectively, 33% and 21% of women had only completed high school. It was not possible to compare data regarding profession, workload, steady partner and children, as Cherick et al 14 , Oliveira et al 15 and Sarwer et al 16 did not address this data in the description of their results. Regarding skin color, data from Oliveira et al 15 showed mixed ethnicity, which does not corroborate the present study.…”
Section: Discussioncontrasting
confidence: 57%
“…According to Cherik et al 14 , Oliveira et al 15 , Sarwer et al 16 , Paul et al 17 , Treacy et al 18 , Janik et al 19 and Assimakopoulos et al 20 , respectively in France, Brazil, North Dakota, Sweden, France, Poland and Greece, the mean age of women who underwent a BS was 39 years, which corroborates the present study, even though one of the studies 19 presents a sample four times larger than this one. The same occurred with marital status and religion, as most women in this study were married and Catholic, as in other studies 14,15,19,20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same authors also found amelioration of several sex positions. As a result, the surveyed women reported adopting a greater variety of sexual positions six months after bariatric surgery [21].…”
Section: Female Sexuality and Sexual Functionmentioning
confidence: 99%